2010
DOI: 10.1007/s10661-010-1634-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of three bivalve species for biomonitoring a polluted estuarine environment

Abstract: Estuaries are marine areas at great contamination risk due to their hydrodynamic features. PAH are wide and ubiquitous contaminants with a high presence in these marine environments. Chemical analysis of sediments can provide information, although it does not give a direct measure of the toxicological effect of such contaminants in the biota. Samples of Venerupis pullastra, Cerastoderma edule, and Mytilus galloprovincialis were collected from two locations in Corcubión estuary (Norhwest of Spain). The level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 59 publications
2
15
0
Order By: Relevance
“…The toxic effects of PAHs depend not only on the availability of the contaminants but also on such factors such as species, photoinduced potential, metabolism, temperature, salinity, and pH. For example, one previous study Fern andez-Tajes et al [19] showed a higher sensitivity of clams and cockles to pollution load levels. Additionally, results from Pelletier et al [60] indicated that the glochidial larvae of Utterbackia imbecillis are sensitive to photoactivated pyrene at environmentally [29].…”
Section: Antioxidant Responses Of P Martensii To Pyrenementioning
confidence: 99%
“…The toxic effects of PAHs depend not only on the availability of the contaminants but also on such factors such as species, photoinduced potential, metabolism, temperature, salinity, and pH. For example, one previous study Fern andez-Tajes et al [19] showed a higher sensitivity of clams and cockles to pollution load levels. Additionally, results from Pelletier et al [60] indicated that the glochidial larvae of Utterbackia imbecillis are sensitive to photoactivated pyrene at environmentally [29].…”
Section: Antioxidant Responses Of P Martensii To Pyrenementioning
confidence: 99%
“…These ratios were usually adopted for PAH in sediments, but they are applicable to different environmental media, [32] such as bivalves (e.g. [4,33]). In all of the expressions, for ease of comparison, PAH ratios have the combustiondominant, thermodynamically less stable isomer in the numerator.…”
Section: August 2015mentioning
confidence: 99%
“…6 , (2004) under study mentioned major influence of ambient dissolved metal concentration and bioaccumulation in two tropical molluscan species. Fern et al, 7 bio monitored concentration of estuarine environment against bivalve species for assessment of biochemical and metabolic changes in the animals. Gagnaire et al 8 have documented depletion of metabolism while studying in vitro effects of heavy metal cadmium and mercury on Pacific oyster, Crassostrea gigas (Thunberg).…”
Section: Introductionmentioning
confidence: 99%